Peningkatan Hasil Belajar Peserta Didik Melalui Model Flipped Classroom pada Pembelajaran Tematik Terpadu di Kelas V SDN 176/IV Kota Jambi - Khairana Fadhilla; Reinita Reinita (Departement of Mathematics Education, 2023)
Based on the results of the researchers' observations and interviews with fifth grade teachers at SD Negeri 176/IV Jambi City which were held from March 23 2022 to March 25 2022, the researchers found that this school had implemented the 2013 curriculum which implemented integrated thematic learning. However, the implementation in the field is not as expected in integrated thematic learning, which requires students to be active and independent in the learning process. Based on these conditions, it is necessary to make improvements and changes in the implementation of the learning process so that the expected integrated thematic learning is realized. One alternative action that can be taken is to apply an effective learning model in the 2013 curriculum, which involves students actively, creatively, independently and fun and makes students able to think critically in dealing with a problem. Among the models that can help is the Flipped Classroom learning model, this model in practice makes students as subjects and students have more social interaction with friends. In the learning process students are actively and independently involved and utilize technology as a medium in learning by watching videos before conducting direct learning.